Assessment of serum interleukin-28 as a biomarker to predict mortality in traumatic patients with sepsis. (September 2022) - Yang, Yang; Chen, Jiajun; Yi, Chengla; Yang, Fan; Tang, Manli; Li, Zhanfei; Bai, Xiangjun
Highlights: IL-28A/B levels were elevated in traumatic patients with sepsis. The non-survivors within 28 days exhibited higher IL-28A/B levels than survivors. IL-28A/B emerged as independent predictors of 28-day mortality in septic patients. Abstract: Background: Serious trauma due to various factors is a major global public issue, and sepsis is a major cause of trauma-associated mortality. Timely diagnosis and suitable treatment of post-traumatic sepsis are crucial to improve the hospital outcome of traumatic patients. IL-28 is a newly discovered member of IFN-λ family with multiple functions in inflammatory response. To date, its role in the pathogenic mechanisms of post-traumatic sepsis still remains unknown. Methods: In total, 20 healthy controls, 55 traumatic patients without sepsis and 54 traumatic patients with sepsis were enrolled in this study. Serum IL-28A/B levels were investigated by ELISA. Results: IL-28A/B levels were significantly increased in traumatic patients compared to healthy volunteers. Moreover, septic trauma patients displayed a significant increase in IL-28A/B levels compared with non-septic patients. In septic patients, IL-28A/B were negatively correlated with IFN-γ, IL-5, IL-13 and IL-17, and positively associated with IL-10. Moreover, IL-28A (AUC: 0.821, 95 %CI: 0.693–0.949) and IL-28B (AUC: 0.811, 95 %CI: 0.691–0.931) were both beneficial to predict increased mortality risk in septic trauma patients, though there was no statistical difference in the predictive value between them. Conclusions: Early serum levels of IL-28A/B were associated with the development of post-trauma sepsis and could be applied to assess the outcome of traumatic patients with sepsis. Thus, IL-28 may be a potential indicator for post-traumatic sepsis.